Pesantren dan pluralisme: Analisis Peran Pesantren Sebagai Katalis Pribumisasi Islam di Indonesia - Hakim, Lutfi (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2021)
Pesantren in Indonesia are a representation of Nusantara Islam which prioritizes tolerance, affirms Islam rahmatan lil 'alamin, with the ideology of tawazun, tawasuth, tasamuh, and i`tidal. Pesantren are ready to provide solutions to the community and are ready to spearhead the cultural Islamic movement and the power of civil society by combining traditional religious knowledge with modern science. Education in pesantren is provided by a representative cleric or kiai who becomes a mentor teacher and role model for students in life. Pesantren education is organized in an orderly manner and takes a long time so that students can gain an in-depth understanding of the essence of everything, making it easier to distinguish between right and wrong. Pesantren since its inception have been very close to the community, because this institution was founded based on a community approach. The presence of pesantren is a carriage that guards the Unitary State of the Republic of Indonesia which is full of multi-racial, ethnic, religious and cultural aspects. The concept of indigenizing Islam in the archipelago has become a jargon for pesantren that must be preserved so that Indonesia, which is multi-religious and cultural, remains safe and does not fall apart. From this short article, the writer wants to see how Islamic boarding schools see and behave towards the problem of religious plurality in Indonesia, which in fact cannot be denied.